Family planning knowledge, attitudes and practices in refugee and migrant pregnant and post-partum women on the Thailand-Myanmar border – a mixed methods study - Salisbury, P; Hall, L; Kulkus, S; Paw, M; Tun, N; Min, A; Chotivanich, K; Srikanok, S; Ontuwong, P; Sirinonthachai, S; Nosten, F; Somerset, S; et al. (BioMed Central, 2016)
Background Lack of data in marginalized populations on knowledge, attitudes and practices (KAP) hampers efforts to improve modern contraceptive practice. A mixed methods study to better understand family planning KAP amongst refugee and migrant women on the Thailand-Myanmar border was conducted as part of an ongoing effort to improve reproductive health, particularly maternal mortality, through Shoklo Malaria Research Unit (SMRU) antenatal and birthing services. Methods Cross-sectional surveys and focus group discussions (FGDs) in currently pregnant women; and in-depth interviews (IDIs) in selected post-partum women with three children or more; were conducted. Quantitative data were described with medians and proportions and compared using standard statistical tests. Risk factors associated with high parity (>3) were identified using logistic regression analysis. Qualitative data were coded and grouped and discussed using identified themes. Results In January-March 2015, 978 women participated in cross-sectional studies, 120 in FGD and 21 in IDI. Major positive findings were: > 90 % of women knew about contraceptives for birth spacing, >60 % of women in the FGD and IDI reported use of family planning (FP) in the past and nearly all women knew where they could obtain FP supplies. Major gaps identified included: low uptake of long acting contraception (LAC), lack of awareness of emergency contraception (>90 % of women), unreliable estimates of when child bearing years end, and misconceptions surrounding female sterilization. Three was identified as the ideal number of children in the crosssectional survey but less than half of the women with this parity or higher in the IDI actually adopted LAC leaving them at risk for unintended pregnancy. Discussing basic female anatomy using a simple diagram was well received in FGD and IDIs. LAC uptake has increased particularly the IUD from 2013–2015. Conclusion Definitive contextual issues were identified during this study and a significant range of action points have been implemented in FP services at SMRU as a result, particularly in regard to the IUD. The importance of the role and attitudes of husbands were acknowledged by women and studies to investigate male perspectives in future may enhance FP practice in this area